THE EFFECTS OF THE QUESUNGUAL AGROFORESTRY SYSTEM OF WESTERN HONDURAS ON SOIL MACROFAUNA - Natasha Pauli; Edmundo Barrios; Thomas Oberthür; Arthur Conacher; Miguel Ayarza; Luis A Welchez (Sociedade & Natureza)
Agricultural practices that promote increased diversity and abundance of soil macrofauna may improve soil quality and productivity, due to the influence of soil macrofauna on organic matter breakdown, nutrient cycling and soil structure. Southern Lempira department in Honduras is an environment where farmers could benefit greatly from such an increase in soil quality. The landscape is hilly, with steep slopes and shallow soils that are susceptible to erosion. The need for shorter fallow periods, a decrease in the use of slash-and-burnagriculture, and promotion by extension agents has resulted in the large-scale adoption of an indigenous agroforestry system known as the ‘Quesungual System’, based on slash-andmulch of vegetation, rotation of maize, sorghum and beans and inclusion of naturally regenerated trees and shrubs within cropped fields. This paper presents research on the effects of four common land use types (secondary forest, recently cleared agroforestry fields, mature agroforestry fields and silvopastoral fields) in the Quesungual area on soil macrofauna abundance and community composition. Sampling methods recommended by the Tropical Soil Biology and Fertility Institute were used to collect soil macrofauna in three representative fields of each type of land use, giving 12 study sites in total. Soil macrofauna communities were highly variable, both within representative fields, between representativefields of the same type, and amongst land uses. Soil macrofauna density ranged from an average of 1637 + 359 individuals m-2 for young Quesungual fields to 831 + 199 individuals m-2 in secondary forest sites. Silvopastoral fields and older Quesungual fields recorded intermediate values of 1508 + 390 individuals m-2 and 1182 + 233 individuals m-2 respectively. Myriapoda and Isoptera were consistently affected by conversion of forest to agricultural land uses, decreasing and increasing in abundance respectively. At depths below 10 cm, soil macrofauna communities appeared relatively similar in all three agricultural uses, but differed from secondary forest. All land uses surveyed contained substantial soil macrofauna communities, which may be the result of incorporation of diverse organic matter inputs in the form of mulch pruned from trees, diverse vegetation and a continuous litter cover.